2008
DOI: 10.1186/1751-0759-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of somatization as a rapid screening tool for mitochondrial dysfunction in depression

Abstract: AimsSomatic symptomatology is common in depression, and is often attributed to the Freudian-inspired concept of "somatization". While the same somatic symptoms and depression are common in mitochondrial disease, in cases with concurrent mood symptoms the diagnosis of a mitochondrial disorder and related therapy are typically delayed for many years. A short screening tool that can identify patients with depression at high risk for having underlying mitochondrial dysfunction is presented.MethodsSix items of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 22 publications
1
34
1
Order By: Relevance
“…Furthermore, the present association of 3010A with nonspecific abdominal pain is consistent with the Boles group's previously reported association of this SNP with both migraine and CVS, conditions in which abdominal pain/discomfort is common. Although prior work has reported an association between mitochondrial dysfunction (as measured by ATP production rate in biopsied muscle) and the presence of somatic symptoms in general (19,20), in the present study, we found no association between the three mtDNA SNPs studied and the overall somatic symptom score. Further research is needed to better understand these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the present association of 3010A with nonspecific abdominal pain is consistent with the Boles group's previously reported association of this SNP with both migraine and CVS, conditions in which abdominal pain/discomfort is common. Although prior work has reported an association between mitochondrial dysfunction (as measured by ATP production rate in biopsied muscle) and the presence of somatic symptoms in general (19,20), in the present study, we found no association between the three mtDNA SNPs studied and the overall somatic symptom score. Further research is needed to better understand these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Depressed patients presenting with somatic complaints also have low ATP production rates in biopsied muscles Boles, 2008a, Gardner andBoles, 2008b). In addition, rates of depression are increased in patients with mitochondrial disorders (Fattal et al, 2007, Koene et al, 2009).…”
Section: Mitochondrial Disturbancesmentioning
confidence: 99%
“…Physio-somatic symptoms are commonly encountered in mitochondrial disorders and quite often show a waxing and waning pattern [105][106][107]. Disorders in mitochondria may cause many different symptoms, from mild photophobia and muscle complaints to cerebellar ataxia and neonatal death [105,106,[108][109][110][111].…”
Section: Physio-somatic Symptoms In Mitochondrial Disordersmentioning
confidence: 99%